Broadly neutralizing antibody responses in the longitudinal primary HIV-1 infection Short Pulse Anti-Retroviral Therapy at Seroconversion cohort. (1st November 2021) - Granger, Luke A.; Huettner, Isabella; Debeljak, Franka; Kaleebu, Pontiano; Schechter, Mauro; Tambussi, Giuseppe; Weber, Jonathan; Miro, Jose M.; Phillips, Rodney; Babiker, Abdel; Cooper, David A.; Fisher, Martin; et al.
Abstract : Objective: Development of immunogens that elicit an anti-HIV-1 broadly neutralizing antibody (bnAb) response will be a key step in the development of an effective HIV-1 vaccine. Although HIV-1 bnAb epitopes have been identified and mechanisms of action studied, current HIV-1 envelope-based immunogens do not elicit HIV-1 bnAbs in humans or animal models. A better understanding of how HIV-1 bnAbs arise during infection and the clinical factors associated with bnAb development may be critical for HIV-1 immunogen design efforts. Design and methods: Longitudinal plasma samples from the treatment-naive control arm of the Short Pulse Anti-Retroviral Therapy at Seroconversion (SPARTAC) primary HIV-1 infection cohort were used in an HIV-1 pseudotype neutralization assay to measure the neutralization breadth, potency and specificity of bnAb responses over time. Results: In the SPARTAC cohort, development of plasma neutralization breadth and potency correlates with duration of HIV infection and high viral loads, and typically takes 3–4 years to arise. bnAb activity was mostly directed to one or two bnAb epitopes per donor and more than 60% of donors with the highest plasma neutralization having bnAbs targeted towards glycan-dependent epitopes. Conclusion: This study highlights the SPARTAC cohort as an important resource for more in-depth analysis of bnAb developmental pathways. Abstract : Supplemental Digital Content is available in the text